Establishing an interoperable clinical trial information system within MIRACUM - Hasselblatt, Hanna; Andrae, Johanna; Tassoni, Adrian; Fitzer, Kai; Bahls, Thomas; Prokosch, Hans-Ulrich; Boeker, Martin (Proceedings of the EFMI 2019 Special Topic Conference Studies in Health Technology and Informatics, 2019)
In the long-run we wish to demonstrate the power of linking clinical trial information to routine health records for straightforward patient recruitment - not only at each single hospital but in a large German consortium (called MIRACUM). In such architecture a hospital wide clinical trial registry (CTR) plays a major role. All such site specific CTR however, also need to be interoperable and support automated data provision for a central MIRACUM wide trial registry. Based on a survey of already existing trial information systems at each partner site and a comparison of their functionality, a joint requirement specification was created, a minimal MIRACUM wide trial core dataset was defined and an architecture was designed in which each MIRACUM partner could keep their autonomous system decision. Partners could however also join forces in a cooperative enhancement of a new open source trial registry. Thus, sites with no trial registry could be supported by the others and synergies used. Finally, the newly developed CTR will allow modular site specific add-ons and can also take over the function of the MIRACUM wide trial registry. In this paper we describe the process, how such a consortium-wide CTR was designed and developed, while always keeping cross-site interoperability as a major requirement.
CRIS-Team Scopus Importer:2019-05-09
Keywords: Clinical trial registry; Health information system; MI-I; MIRACUM